Pengembangan Sistem Manajemen Bisnis Katering Rumahan Berbasis Web (Studi Kasus: Senjani Kitchen) - Andika Putra Sadewa; Adam Hendra Brata; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Senjani Kitchen is a catering service based in Malang, East Java which provides delivery services inside and outside the city. Almost every day there are always order transactions made by customers. That's make a lot of value and financial benefits, but suggests that there are some problems in some of the ongoing business processes. Some processes that have problems are the process of recording the orders and the bento or lunch boxes. The recording process is done manually using paper notes and with Microsoft Excel programs, so that there is often a loss of information between employees working on orders. The problems of management and business will be solved with development of a system. Development is carried out by applying the waterfall method because the features or system requirements have been defined in the requirement analysis based on the agreement between the user and the developer. The requirement analysis process is explain the features and functionality of a business management system catering, and the result is based on the problem of business process. After the requirement process they are a design process for implementing the requirement to the actual system. Program code will be implemented using the PHP programming language. System validation is done by means of testers which are carried out by two methods, unit testing, and validation testing. The results of the unit and validation testing produce 100% validity, so this business management system has met and is in accordance with user requirement.